Photographic Image of Cities: From Admiration to Anxiety - Lechowicz, Lech (Porównania, 2024)
The subject of this text is the description of the evolution of photographers’ attitudes towards the city, expressed in images whose subject is both the material and human urban fabric. The chronological scope covers the period from the mid-nineteenth century to the turn of the 1960s and 1970s. The geographical scope includes Europe and the USA.